Pengaruh Karakteristik Pekrjaan dan Stres Kerja Terhadap Perilaku Kerja Kontraproduktif Karyawan PT. Telkom Datel Mamuju - Chaerunnisa, Aulia; Aqil, Muhammad; Barung, Rachmat; Abdullah, M Said (Journal of Management Branding, 2024)
This research was conducted with the aim of determining the influence of job characteristics and work stress on counterproductive work behavior PT Telkom Datel Mamuju. This research uses quantitative methods, the research sample uses a total sampling technique with a total of 42 respondents. Data collection was carried out by observation, interviews, document analysis, and distributing questionnaires directly to respondents. Testing the quality of research instruments uses validity and reliability tests. The analytical tool used is multiple linear regression analysis, then testing the hypothesis using a partial test (t statistical test), simultaneous test (F statistical test), and to determine the contribution of the independent variable to the dependent variable using the coefficient of determination.The research results obtained: (1) Job characteristics do not have a significant effect on counterproductive work behavior; (2) Job stress has a significant effect on counterproductive work behavior; (3) Job characteristics and work stress simultaneously have a significant effect on counterproductive work behavior. Meanwhile, the contribution of job characteristics and work stress to employee counterproductive work behavior is classified as moderate with a percentage of 48.1%, which means there are still 51.9% other factors that can influence counterproductive work behavior PT Telkom Datel Mamuju